Toxicity Assessment of Wild Mushrooms from the Western Ghats, India: An in Vitro and Sub-Acute in Vivo Study - Sai Latha, S.; Naveen, S.; Pradeep, C. K.; Sivaraj, C.; Dinesh, M. G.; Anilakumar, K. R. (Frontiers in Pharmacology, 2018)
Background: Poisoning by different kinds of toxic mushrooms is unfortunately becoming an increasingly important medical problem, evident from the growing number of reports worldwide since the 1950s.Mycetism being a health concern, deserves scientific attention. In this perspective, the present study aims to assess the potential effects of ingesting the selected wild mushrooms from regions of the Western Ghats, India Methods: The preliminary cytotoxicity of the selected mushrooms was studied in vitro on the intestinal NCM460 and the Chang’s liver cell lines on the basis of cell viability. Further, the hepatotoxicity was assessed by measuring biologically relevant endpoints such as membrane integrity, mitochondrial stress and oxidative status. A 28 day sub-acute toxicity study was carried out by orally administering the mushroom extracts to mice at 250 and 500 mg/kg body weight. The haematological and serum analysis as well as histological examinations were carried out to evaluate their in vivo toxicity. GC-MS analysis of the mushrooms facilitated the identification of their volatile chemical profile. Result: The in vitro intestinal cytotoxicity exhibited by these wild mushrooms in comparison to the edible mushroom indicated their potential gastrointestinal toxicity. The pathological findings in `small intestine on exposure to Chlorophyllum molybdites and Agaricus endoxanthus also validates the speculations about their intestinal toxicity. The toxic insult to the hepatocytes due to Amanita angustilamellata, Entoloma crassum and Clarkeinda trachodes was predictive of the observed in vivo hepatotoxicity which was also accompanied by renal toxicity at the higher dose of 500mg/kg bwt. Conclusion: The potential toxicity exhibited by these representative mushrooms from the wild warrants caution about their consumption. The present work could also have broader implications for global mycetism.